Religious Inclusivism In Indonesia: Study Of Pesantren An-Nida And Edi Mancoro, Salatiga, Central Java Indonesia (Ushuluddin International Conference (USICON), 2017)
This abstract is the result of research intended to elaborate the students' religious inclusiveness in the Nida and Edi Islamic boarding schools (Pesantren) of Salatiga, Central Java. In its descriptive analysis, this paper will try to elaborate a phenomenon or social unit of religious life in boarding schools in which some research instruments such as participant observation, open interviews and unstructured questionnaires are used. The results showed that: , there was a shift from the structured theoretical foundation both in Islamic boarding schools of Edi Mancoro and An Nida, an overview of students' religious inclusiveness appearing in the form of culture, namely: cultural preservation to cultural transformation. The cultural forms emerge because the existence and function of religion (Islam) transforms into the culture while religion is analyzed from the perspective of the local culture. The cultural and transformative inclusiveness is generated by the particularity of students' religious and educational traditions although they maintained but they have also experienced changes; and openness to adapt and impart through a transformative social process. This transformation causes the emergence of collectively cultural values agreed and implemented together, thus they are universal. The students' tradition preservation is determined by two mutually linked variables namely: 1) kiais as guardians of tradition, and 2) curriculum that maintains the teaching of classic book (Kitab Kuning (yellow book) as a buffer tradition. While the changes of tradition are also influenced by two variables, namely 1) social interaction with the surrounding local culture of the boarding schools, and 2) the students' communication patterns with their external plural environment. , the students' preserved and changing traditions produced a unique religious authority . In the Pesantren An Nida, religious authority was manifested from the supremacy of fiqh (Islamic jurisprudence) enlightened by ijtihad (rational reasoning). There is a reciprocal relationship between fiqh and ijtihad, so that the dynamic verbal nature of fiqh will appear. The rational values in ijtihad was then strengthened
Keywords: inclusivism-transformative, Islamic religious authorities in Indonesia, Pesantren, local culture